Biosynthesis and biological function of secondary metabolites of the rice blast fungus Pyricularia oryzae. (11th August 2021) - Motoyama, Takayuki; Yun, Choong-Soo; Osada, Hiroyuki
Abstract: Filamentous fungi have many secondary metabolism genes and produce a wide variety of secondary metabolites with complex and unique structures. However, the role of most secondary metabolites remains unclear. Moreover, most fungal secondary metabolism genes are silent or poorly expressed under laboratory conditions and are difficult to utilize. Pyricularia oryzae, the causal pathogen of rice blast disease, is a well-characterized plant pathogenic fungus. P. oryzae also has a large number of secondary metabolism genes and appears to be a suitable organism for analyzing secondary metabolites. However, in case of this fungus, biosynthetic genes for only four groups of secondary metabolites have been well characterized. Among two of the four groups of secondary metabolites, biosynthetic genes were identified by activating secondary metabolism. These secondary metabolites include melanin, a polyketide compound required for rice infection; tenuazonic acid, a well-known mycotoxin produced by various plant pathogenic fungi and biosynthesized by a unique nonribosomal peptide synthetase–polyketide synthase hybrid enzyme; nectriapyrones, antibacterial polyketide compounds produced mainly by symbiotic fungi, including plant pathogens and endophytes, and pyriculols, phytotoxic polyketide compounds. This review mainly focuses on the biosynthesis and biological functions of the four groups of P. oryzae secondary metabolites.